Service Providers' Attitudes Toward Athletes With Eating Disorders. Issue 1 (January 2018) - McArdle, Siobhain; Meade, Mary M.; Burrows, Emma
Abstract : Objective: This study explored the nature and extent of Athlete Support Personnel's (ASP's) attitudes and beliefs toward athletes with symptoms of anorexia nervosa (AN) compared with those with symptoms of depression. Design: A cross-sectional study with a survey instrument. Setting: Sport and Exercise Science Professional Bodies and Associations in the Republic of Ireland, Northern Ireland, and mainland United Kingdom. Participants: One hundred fifty-two ASP. Main Outcome Measures: Participants read 2 vignettes describing a fictional female athlete with symptoms of AN or depression after which they completed an on-line survey examining attitudes toward such athletes. Results: Significant differences in patterns of responses were found between the 2 mental health conditions. The athlete with AN was viewed as significantly more difficult to communicate with F (1, 148) = 18.17, P = 0.000, η 2 = 0.11, more likely to be using her disorder to gain attention F (1, 148) = 21.69, P = 0.000, η 2 = 0.13, personally responsible for her condition F (1, 148) = 10.10, P = 0.00, η 2 = 0.06, and less likely to recover F (1, 148) = 23.03, P = 0.000, η 2 = 0.14 than the athlete with depression. Male service providers were more likely to believe that the athletes depicted were attention seeking F (1, 148) = 10.69, P = 0.001, η 2 = 0.07 and only had themselves to blame for their mental health condition F (1, 148) = 12.97, P = 0.000, η 2 = 0.08. Conclusions: Athlete support personnel report stigmatizing attitudes toward athletes with eating disorders such as AN. Male service providers hold greater negative attitudes toward athletes with mental health conditions.